Road Traffic Related Injury Research and Informatics - Al-Shorbaji, N.; Haux, R.; Krishnamurthy, R.; Marschollek, M.; Mattfeld, D. C.; Bartolomeos, K.; Reynolds, T. A. (Methods of Information in Medicine, 2015)
The United Nations has recently adopted 17 sustainable development goals for 2030, including ensuring healthy lives and promoting well-being for all at all ages, and making cities and human settlements inclusive, safe, resilient and sustainable. Road injuries remain among the ten leading causes of death in the world, and are projected to increase with rapidly increasing motorisation globally. Lack of comprehensive data on road injuries has been identified as one of the barriers for effective implementation of proven road safety interventions. Building, linking and analysing electronic patient records in conjunction with establishing injury event and care registries can substantially contribute to healthy lives and safe transportation. Appropriate use of new technological approaches and health informatics best practices could provide significant added value to WHO’s global road safety work and assist Member States in identifying prevention targets, monitoring progress and improving quality of care to reduce injury-related deaths. This paper encourages the initiation of new multidisciplinary research at a global level.© World Health Organization 2015. All rights reserved.The World Health Organization has granted Schattauer Publishers and the authors permission for the reproduction of this article.The authors alone are responsible for the views expressed in this article and they do not necessarily represent the views, decisions or policies of the institutions with which they are affiliated.
Keywords: Medical informatics; biomedical informatics; health informatics; accident research; injury research; multidisciplinary research